2018
DOI: 10.31539/leea.v2i1.453
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Figurative Language Used in Edgar Allan Poe’s Poems

Abstract: The objectives of the research was to describe kinds and meanings of figurative language used in Edgar Allan Poe’s poems. The titles of the 8 Edgar Allan Poe’s poems were “Annabel Lee, The Sleeper, A Dream Within A Dream, To One in Paradise, Alone, Spirit of the Death, The Lake and Evening Stars”. Descriptive qualitative method was used to classify and analyze the data. The technique used in collecting the data was library research. Meanwhile, in analyzing the data, the researchers applied qualitative descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We can also see that figurative language can be applied in short fiction, poetry, and drama in literary works. Syafitri and Marlinton (2018) stated that in poems, ideas and feelings are packed into a few lines. As we can see, there are some types of figurative languages: metaphor, simile, hyperbole, personification, sarcasm, irony, idiomatic expression, metonymy, etc.…”
Section: A Introductionmentioning
confidence: 99%
“…We can also see that figurative language can be applied in short fiction, poetry, and drama in literary works. Syafitri and Marlinton (2018) stated that in poems, ideas and feelings are packed into a few lines. As we can see, there are some types of figurative languages: metaphor, simile, hyperbole, personification, sarcasm, irony, idiomatic expression, metonymy, etc.…”
Section: A Introductionmentioning
confidence: 99%
“…Illustrative subjective strategy was utilized to characterize and dissect the information. The strategy utilized in gathering the information was a library to explore figurative language in his poetry by qualitative terminologies (Syafitri, 2018). A researcher observed that Poe has recognized certain words by placing them in italics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author writes "So I had Hiroko and Konrad's relationship developed around Konrad's need for a translator who knew both Japanese and German. But as often happens with novels that plot device quickly became a troupe of the novel -a symbol of various characters' willingness to enter different worlds and experiences and make them their own" [20].…”
Section: Introductionmentioning
confidence: 99%